Microstructural study of dielectric breakdown in glass-ceramics insulators. Issue 2 (February 2019) - Fuertes, V.; Cabrera, M.J.; Seores, J.; Muñoz, D.; Fernández, J.F.; Enríquez, E.
Abstract: Novel glass-ceramic materials based on Na and Ca-rich feldspar crystallizations with a hierarchical micro-nanostructure shown the largest dielectric strength, >57 kV/mm, reported at room temperature in ceramic insulators, due to a large amount of interfaces that favor scattering processes of charge carriers. Dielectric breakdown tests with temperature indicated they withstood up to 200 °C, with dielectric strengths of 30 kV/mm and 44 kV/mm for anorthite and albite-based glass-ceramics, respectively. These values are even larger than the ones obtained at room temperature for most of the current ceramic insulators. Microstructural characterization and micro-Raman spectroscopy carried out after breakdown allow determining the dielectric breakdown mechanisms. Glass phases in the surroundings of the crater because of local melting and fast cooling are identified. These results make feldspar based glass-ceramics suitable for electrical insulator applications at room and high temperature. Moreover, dielectric breakdown mechanism may allow tailoring new high insulating application in the future.